Effects of Tumor Microenvironment on the Primo Vascular Pattern in the Mouse Model of Metastatic Breast Cancer - Amir Atashi; Mohammad Kamalabadi-Farahani; Nariman Rezaei Kolarijani (Medical Association of Pharmacopuncture Institute, 2024)
Background : Tumor survival, promotion, and metastatic functions are regulated by the tumor microenvironment (TME). The primo vascular system (PVS), the third circulatory system in animals, is currently thought to be a highly effective pathway for the spread of cancer cells. Objectives: In the present study, we intend to determine the TME effects on the PVS pattern in breast cancer for the first time. Methods : Heterotopic and orthotopic metastatic triple-negative breast cancer (TNBC) mice models were created. After 35 days, the skin was retracted, and a 2 cm skin incision was made up and down from the surface of the tumor tissue. In preparation for PVS staining, the dyes (trypan blue and alamarBlue) were injected throughout the tumor tissues. Under a stereomicroscope, PVS in heterotopic and orthotopic tumors was seen. Results : According to our data, there are no appreciable variations in PVS patterns and density between heterotopic and orthotopic animal models. Furthermore, alamarBlue is a good option for tumor PVS staining, as demonstrated by our research. Conclusion : For the first time, our data gave significant new information about the PVS in TNBC. Creating new anti-cancer treatments may be made possible by a better understanding of the biological characteristics of the TME and PVS.